Penyuluhan Potensi Pengembangan Agroforestri Berbasis Umbi-Umbian sebagai Bahan Pangan Alternatif di Desa Pandankrajan Kemlagi Mojokerto - Anam, Khoirul; Purwanti, Sri; Novita, Mega D; Soesanto, Soesanto; Ikka, Ni Dewi Ambal; Utomo, Budi; Kusumawati, Nur Farida; Aditya, Dipa; Mulyono, Joko Sri (Pakis Journal Institute, 2025)
Pandankrajan Village, Kemlagi District, Mojokerto Regency, has a social forestry area managed collaboratively with PT. Perhutani, offering potential for agroforestry development. However, community land use for intercropping (e.g., corn and cassava) remains suboptimal. This community service program aims to enhance land productivity by introducing Xanthosoma undipes (Beneng taro) as an agroforestry-based intercrop. The community service activities were conducted from April 21 to 25, 2025, with methods included: (1) coordination with farmer groups and land mapping, (2) socialization of Beneng taro cultivation techniques, (3) field surveys for land suitability analysis, (4) hands-on agroforestry training, and (5) participatory evaluation with farmers.** Beneng taro was selected for its shade tolerance, high economic value, and potential as an alternative food source. Results showed farmers' enthusiasm in adopting cultivation techniques and recognizing its economic benefits. The program is expected to strengthen food security, increase income, and promote environmental conservation through sustainable agroforestry. Stakeholder collaboration and technological innovation are key to ensuring long-term sustainability.